2021
DOI: 10.1177/1179551421990678
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Glycemic Control in Saudi Children with Type 1 Diabetes at Different Developmental Age Groups

Abstract: Background: Children with type 1 diabetes (T1D) at different stages of development have age-specific needs, which can influence their perception of quality of life (QoL). In our study, we aimed to emphasize these age-specific needs and assess the perception of QoL in Saudi children with T1D, as well as their parents correlating QoL scores with children’s glycemic control. Methods: This is a cross-sectional study in which children with T1D and their parents from 2 tertiary institutes in Saudi Arabia have answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
3
14
0
1
Order By: Relevance
“…An analysis from the SEARCH for Diabetes in youth investigating discrepancies in parent-proxy and youth reported quality of life also showed that quality of life perceptions between caregivers and youth differ significantly ( 25 ). This is in line with a more recent study showing significantly different quality of life between children and parents ( 26 ). Johnson et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An analysis from the SEARCH for Diabetes in youth investigating discrepancies in parent-proxy and youth reported quality of life also showed that quality of life perceptions between caregivers and youth differ significantly ( 25 ). This is in line with a more recent study showing significantly different quality of life between children and parents ( 26 ). Johnson et al.…”
Section: Discussionsupporting
confidence: 93%
“…An analysis from the SEARCH for Diabetes in youth investigating discrepancies in parent-proxy and youth reported quality of life also showed that quality of life perceptions between caregivers and youth differ significantly (25). This is in line with a more recent study showing significantly different quality of life between children and parents (26). Johnson et al found in their cross-sectional study with 325 children and their parents, that children and parents with the greatest FOH reported a significantly reduced quality of life (9).…”
Section: Discussionsupporting
confidence: 78%
“…There was negative correlation between diabetic-specific routine for adolescents with type 1 diabetes mellitus and their insulin doses daily (r=-0.351; p=0.000). this results are agreeing with study (20) which revealed that 288 proxy and self-reports were collected from 144 children with T1D in three age groups: (49%) from 8 to 12 years, (7%) from 5 to 7 years, and (44%) from 13 to 18 and their parents. In the whole comprehensive and domain scores, there was a major difference in QOLbetween proxy reports and self.…”
Section: Discussionsupporting
confidence: 92%
“…SPSS version (20) and Microsoft Excel (2010) programs to statistically analyze the data collected from the study sample, find the relationships between the variables and obtain the research's final results based on a set of statistical tests.…”
Section: Methodsmentioning
confidence: 99%
“…При изучении КЖ у детей дошкольного возраста были получены результаты, свидетельствующие о том, что представления родителей о КЖ ребенка в целом и оценки влияния заболевания на КЖ были ниже, по сравнению с оценками самих детей с СД1, при этом дети приводили более низкие оценки своего эмоционального благополучия. Эти различия подчеркивают важность исследований, направленных на субъективную оценку факторов, связанных с болезнью, как самими пациентами, так и их родителями [5][6][7][8].…”
unclassified